Teknik Penggambaran Doodle Pada Batik Lukis untuk Scarf - Maria Fransiska Ratri Wulandari Suhartomo; Theresia Widyastuti (Pusat Penerbitan LP2MPP ISI Denpasar, 2022)
One of the efforts of batik preservation is developing several aspects in it, such as developing the pattern. The main motif of designing batik Lukis is in the form of marine life depicted with the drawing doodle technic. With theories batik, doodle, also drawing tehnics. This design of scarf product is for women, adults or teenager as an innovation of existing batik motifs and is expected to be an alternative product that can keep up the times. The design scarf product is made using the design process approach and it goes through four steps such as, starting form identifying the problem which have existed before in developing batik. Then, analizying the product planning according to the target market. After that, carrying out the creative process and proceed to the production process. Benefits from this producs use for inner and outer.